Analysis Of Accounting Information System at PT. Jasaraharja Putera Branch of Bengkulu - Faizal Rekon Sirnandi; Ida Anggriani; Zahrah Indah Ferina (Penerbit Jurnal Indonesia, 2021)
The purpose of this study to analyze the accounting information system at PT. Jasaraharja (Putera) Bengkulu Branch in accordance with SAK ETAP in 2020. This type of research is descriptive. Data collection techniques using interviews and observation. The analytical method used in this study is a comparative method, which is to compare the recognition of income and expenses by PT. Jasaraharja (Putera) Bengkulu Branch which has been applied and compared to revenue and expense recognition in accordance with SAK ETAP no. 11 of 2009. The results showed that the recognition of income from demand deposits, administrative income of PT. Jasaraharja (Putera) Bengkulu Branch is still not in accordance with SAK ETAP regulations because the method used tends to be on a cash basis, because based on SAK ETAP revenue recognition must use an accrual basis. Recognition of expenses on PT. Jasaraharja (Putera) Bengkulu Branch has complied with SAK ETAP because expenses are recognized on an accrual basis and are recognized at the end of the period, all expenses incurred in PT. Jasaraharja (Putera) Bengkulu Branch has been included in the income statement for each period. There is a discrepancy between the revenue recognition between PT. Jasaraharja (Putera) Bengkulu Branch with SAK ETAP and the suitability between the recognition of expenses between PT. Jasaraharja (Putera) Bengkulu Branch with SAK ETAP.